Serviceability Analysis of Pedestrian Overhead Bridges and Underpasses - Fazal E. Ghafoor; Malik Sarmad Riaz; Ahmed F. Deifalla; Marc Azab; Omer Javaid; Muhammad Nouman Sattar; Muhammad Maqbool Sadiq (Salehan Institute of Higher Education, 2023)
A grade-separated crossing allows a bicycle/pedestrian to continue over or under a barrier without conflict with a vehicle. However, the serviceability of these facilities is compromised in underdeveloped countries, including Pakistan. This research examines the effectiveness of pedestrian bridges and underpasses in terms of their usage by pedestrians. A total of 80,017 pedestrian crossings were observed at four sites (3 overhead bridges and one underpass) for four weeks (one week per site) using manual and video photography. The data about age, gender, and serviceability of each pedestrian was collected and analyzed using the chi-square test, t-test, and descriptive analysis. The study site selection was based on different characteristics, i.e., the number of lanes, type of median barriers, and type of facility (bridge/underpass). The analysis shows that most of the pedestrians (71.83%) did not use the crossing facilities, resulting in the poor serviceability of these structures. A comparison between bridges and underpasses also reveals that underpass usage (62.5%) is statistically more significant than bridge usage (11.62%). There is an effect of age (p<0.001) and gender (p<0.001) on the serviceability of these facilities as well, with pedestrians aged more than 25 years old and females using the facilities more than their counterparts. The study also provides implications for the effect of barriers and the height of facilities on the serviceability of these facilities. The number of lanes and the presence of a median barrier, as well as the height of the facility (number of steps), are the primary factors influencing the serviceability of grade-separated pedestrian crossings. Doi: 10.28991/CEJ-2023-09-04-09 Full Text: PDF